Ekspresi Spiritualitas Kelompok Keagamaan di Beberapa Wilayah Provinsi Aceh - Hanif Saputra (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
This study aims to explore the existence of diverse religious groups in the province of Aceh and how they engage in religious activities alongside other groups. In collecting data, the researcher used the library research method to gather references from books, journals, and academic research reports related to the topic, as well as the Netnography method to gather public information through relevant social media. The results show that there are several different religious groups in Aceh with varying views and expressions of their rituals in different regions. The Tastafi group, Jama'ah Tabligh, and the T. Raja Ubiet community group have different characteristics and expressions in their spiritual activities. On the other hand, the Wahabi group shows a far different view from the local spiritual practices, causing them to be isolated from other religious groups. This study reinforces the reality that although Aceh has implemented Islamic law as positive law, religious groups can still thrive and not hinder the emergence of various religious expressions in the community. Abstrak Kajian ini bertujuan untuk mengeksplorasi tentang eksistensi beragam kelompok keagamaan di Provinsi Aceh dan bagaimana mereka melakukan aktivitas keagamaan secara berdampingan dengan kelompok lainnya. Dalam pengumpulan data, peneliti menggunakan metode library research yang mengumpulkan referensi dari buku, jurnal, dan laporan penelitian akademik yang berhubungan, serta metode Netnografi yang mengumpulkan informasi publik melalui media sosial yang relevan. Hasil penelitian menunjukkan bahwa terdapat beberapa kelompok keagamaan yang berbeda dalam pandangan dan ekspresi ritual mereka di beberapa wilayah Aceh seperti kelompok Tastafi, Jamaah Tabligh, dan kelompok masyarakat T. Raja Ubiet. Kajian ini mempertegas realitas bahwa meskipun Aceh telah menerapkan syariat Islam sebagai hukum positif, namun kelompok keagamaan tetap dapat berkembang dan tidak menghalangi lahirnya berbagai ekspresi keagamaan dalam masyarakat.